The Need for Updated and Electronically Published Codes of Ethics: Lessons from Kuwait. (2nd January 2023) - Zamoon, S.
Abstract: A code of ethics can guide employees to what an organization deems ethical. A code of ethics can reduce ambiguity introduced by Information Technology (IT), decouple employees from individual Ethical Decision-Making (EDM), and remove reliance on laws that lag organizational practices. Herein, the background explains the impetus for organizations having an online code of ethics, and why the public sector is susceptible to ethical violations. The focus is on The State of Kuwait where, despite existence of Kuwait's anti-corruption agency (Nazaha) and the UN's anti-corruption agreement, ethical violations are widely reported. We investigate 87 government entities in Kuwait and find a shortage of online codes. The study's contribution lies in the integration of disparate research, the application to a novel domain (government entities in Kuwait), and education of regulators by pinpointing actions that can influence reform. The study has managerial implications and is a cornerstone for the requirements of anti-corruption and transparency agencies. Although the scope is finite, it may be culturally relevant to Gulf States within the region and the wider Arab world.